DISARMING WORDS: PRE-SERVICE TEACHERS’ PEDAGOGICAL APPROACHES IN CATAPULTING LANGUAGE SENSITIVITY TOWARD A HARMONIZED INSTRUCTIONAL PLAN - Normita Lugtu; Ryan Pecson (International Journal of Teaching and Learning, 2025)
Words, as a double-edged sword, can make or break a child. As society and education progress, inclusivity in diversity has become the norm, mandating that academic institutions and educators become more responsive to progressive approaches in instructional delivery, thereby contributing further to SDG No. 4 (Quality Education) and statutory and regulatory requirements. However, limited studies highlight the need for preparatory practices to equip future educators to foster inclusive education. With that information, the study examines the pedagogical approaches of pre-service teachers in promoting language sensitivity practices among public secondary students during their internship program, employing a descriptive survey design in quantitative research. The study focuses on (i) the profile of pre-service teachers; (ii) their pedagogical approaches used, (iii) the significant difference in their practices, and (iv) the proposal of a harmonized instructional plan. Eighty (80) pre-service teachers, comprising 65 females and 15 males, who are deployed to public secondary schools in the City of Balanga and Bataan, Philippines, and who handle students in Grades 7 to 10, are purposively selected to serve as respondents for the survey. Upon validation and reliability assertion of the research instruments, data gathering commenced, assuring compliance with stringent research protocols (i.e., anonymity, consent, and data confidentiality). Descriptive and inferential statistics are employed to analyze the data. The findings reveal that pre-service teachers are predominantly female and typically handle higher grade levels (Grades 9 and 10), with a high utilization of approaches to promote language inclusivity. A significant difference in their practice is observed when grouped by sex, while there is no significant difference in terms of the year level handled. At the outset, a comprehensive, harmonized instructional plan is introduced.